Dynamic estimation of emittance growth with tune depression and nonlinear field energy factor during longitudinal bunch compression for heavy ion inertial fusion driver - Kikuchi, Takashi; Horioka, K. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
In general, the radial matched beam is according to an equilibrium condition, and depends on the radial (transverse) confinement force and the ratio of repulsion forces between the space charge potential and the thermal pressure [1-3]. During longitudinal bunch compression, parameters of charged particle beams are changed, and the beam current is also increased due to the increase of the charge density...
Keywords: dynamic estimation; equilibrium condition; radial matched beam; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics